Design, construction and commissioning of a technological prototype of a highly granular SiPM-on-tile scintillator-steel hadronic calorimeter - White, Andy; Yu, J.; Briggl, Konrad; Eckert, Patrick; Munwes, Yonathan; Schultz-Coulon, Hans-Christian; Shen, Wei; Stamen, Rainer; Tarkovsky, E. (Journal of Instrumentation, 2023)
The CALICE collaboration is developing highly granular electromagnetic and hadronic calorimeters for detectors at future energy frontier electron-positron colliders. After successful tests of a physics prototype, a technological prototype of the Analog Hadron Calorimeter has been built, based on a design and construction techniques scalable to a collider detector. The prototype consists of a steel absorber structure and active layers of small scintillator tiles that are individually read out by directly coupled SiPMs. Each layer has an active area of 72 × 72 cm^2 and a tile size of 3 × 3 cm^2. With 38 active layers, the prototype has nearly 22,000 readout channels, and its total thickness amounts to 4.4 nuclear interaction lengths. The dedicated readout electronics provide time stamping of each hit with an expected resolution of about 1 ns. The prototype was constructed in 2017 and commissioned in beam tests at DESY. It recorded muons, hadron showers and electron showers at different energies in test beams at CERN in 2018. In this paper, the design of the prototype, its construction and commissioning are described. The methods used to calibrate the detector are detailed, and the performance achieved in terms of uniformity and stability is presented.
Published 22 November 2023
Gesehen am 27.02.2025
The CALICE Collaboration: A.White, K. Briggl, P. Eckert, Y. Munwes, H.-Ch. Schultz-Coulon, W. Shen, R. Stamen [und viele weitere]